Effects of saffron (Crocus sativus) petal ethanolic extract on hematology, antibody response, and spleen histology in rats - Atefeh Babaei; Javd Arshami; Alireza Haghparast; Mohsen Daneshmesgharan (Mashhad University of Medical Sciences, 2014)
Objective: Saffron petal is a by-product that contains flavonoids and anthocyanins. In order to study the effects of saffron petal extract (SPE) on blood parameters, immune system, and spleen histology, five treatments (n=6) were used in a completely randomized design. Materials and Methods: The treatments were 0, 75, 150, 225, and 450 mg/kg body weight of SPE. The SPE was injected intraperitoneally to 30 rats (10-week old, weighing 225±15 g) for 14 days. Immunization was performed using 1×108 sheep red blood cells (SRBC) on days 0 and 7 subcutaneously in all treatment groups. On day 15, blood was collected from the heart of rats after anesthesia. One part of samples were poured in heparinized tubes for counting whole blood cells (CBC) and different white blood cells (WBC) and the other part was used to measure IgG using ELISA technique. The spleen was stained by hematoxylin- eosin for histological study. The data were statistically analyzed using ANOVA program and the means evaluation was done using Tukey's test. Results are presented as mean±SD. Results: Results showed no significant difference between treatments and control group regarding the amount of RBC, HGB, HCT, and PLT. The level of IgG at 75 mg/kg was significantly increased in comparison with other groups. No changes were observed in spleen histology. Conclusion: The results indicate that use of SPE at dose of 75 mg/kg causes an increase in antibody response without any change in hematological parameters and spleen histology.